Democracy in the Grip of Power: A Case Study of the Replacement of Candidates and Unilateral Dismissal by the Aceh Party in the Legislative Election of the Aceh House of Representatives (DPRA) in the 5th Constituency 2024-2029 - Yayang Firdianda Cantika; Robi Cahyadi Kurniawan; Ahmad Harakan; Paryanto (Journal of Governance and Social Policy, 2026)
The 2024 Aceh People's Representative Council (DPRA) legislative election was marked by the emergence of nepotism and political dynasty practices that harmed democracy, this was seen in the process of replacing legislative candidates through PAW and the unilateral dismissal of three cadres by the Chairman of the Aceh Party. This study aims to describe the process of replacing legislative candidates (caleg) and unilateral dismissals that occurred within the Aceh Party and analyze the political and social implications arising from these events. The research method used is a descriptive qualitative method based on document study. Data collection was carried out by searching for documents in the form of a recapitulation of the Aceh Party's vote acquisition in Electoral District 5, as well as news and articles related to the replacement of legislative candidates through the PAW mechanism and the unilateral dismissal of legislative candidates. The collected data will then be further analyzed through a qualitative approach with content analysis techniques. Based on the analysis that has been done, it shows that the replacement of Aceh Party legislative candidates in Electoral District 5 indicates a decline in local democracy. The dismissal of three legislative candidates with the most votes to support a seat for the wife of the Aceh Party chairman demonstrates the practice of nepotism and dynastic politics that harm the principle of public representation. The impact of this action also caused a structural crisis within the Aceh Party and affected public participation.